The Breivik case and the comparative issues of criminal (in)sanity - Burazer, Mislav (Array, 2020)
In the summer of 2011, Anders Behring Breivik committed a terrorist attack in Norway in which 77 people were killed, and at least 319 more were injured. This paper analyses several aspects of the deadliest attack on European soil since World War II, primarily the psychological background of this crime and its legal implications. The paper consists of three sections. The first section presents the comparative and legal basics of criminal insanity that is necessary in order to understand the sections that follow. The second section deals with the perpetrator’s psychological profile and the great debate that had ensued due to the contradicting reports of the Norwegian experts. The last section of the paper summarises the essence of the previous two sections while presenting a comparative procedural analysis of hypothetical trials in select jurisdictions. This paper is based on a comparative analysis of legal norms that aims to highlight the high complexity of the issue. The Breivik case has been selected as an ideal example because, on the one hand, it has created a number of contradicting opinions within its domestic legal system while, on the other hand, its universal nature makes it suitable for a more complex comparative analysis.